MUSLIM AWAM DAN FATĀWĀ AL-NAWĀZIL: ANTARA MAṢLAḤAH DAN MASALAH - Arifana Nur Kholiq; Maskur Rosyid (Journal of Islamic Studies and Humanities, 2022)
Legal certainty is needed so that order can be realized. One of the efforts that can be done is positive integration between the government and the ulama in determining the competence of a muftī. This article provides discourse and solutions regarding the criteria for a muftī in providing legal answers in extraordinary cases (nawāzil). Ordinary Muslims in this matter become an important concern, because they need legal certainty from experts. Wrong in seeking legal solutions, of course, has an impact on legal misguidance. More than that, the phenomenon of the emergence of an impromptu muftī, of course, can cause legal chaos. Through a literature study, this paper concludes that the presence of a credible muftī and fatwā institution is a must for a country, so that legal products that realize the benefit of the people can be realized.